The Development of the Current Da'wah Model through the Diagnosis Counseling Technique of the 10 Big Sins - Khilman Rofi Azmi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2019)
The dynamics and needs of the Islamic community are developing by the demands of the times. This article aims to create an alternative model of da'wah to answer the needs of the Islamic community, especially for the millennial generation. The da'wah model is practical and focuses on solving problems through the diagnosis of 10 significant sins which including Syirik, Leave the Sholat, Disobedience to parents, Adultery, Eating illegitimate or Haram (assets of orphans), Drinking Khamr, Deciding of Silaturahm (Moslem Relationship), Fake Oaths, Miser; and Slandering. The present model of da'wah through the diagnosis technique of 10 major sins is designed by integrating the "person to person" communication and counseling approach with the principle of empathy and unconditional acceptance. The use of new terms refers to the use of various social media platforms to encompass the public to fulfill devotional da'wah for the Ummah.Penelitian ini bertujuan untuk mengembangkan model alternatif dakwah guna menjawab tuntutan masyarakat Islam, khususnya bagi generasi milenial. Model dakwah praktis dan menitikberatkan pada penyelesaian masalah melalui diagnosa 10 dosa besar yang meliputi; Syirik, Tinggalkan Sholat, Ketidakpedulian terhadap orang tua, Perzinahan, Makan haram, Minum Khamr, Penetapan Silaturahm, Sumpah Palsu, Pelit dan Fitnah. Model dakwah saat ini melalui teknik diagnosis 10 dosa besar dirancang dengan integrasi pendekatan komunikasi dan konseling “orang ke orang” dengan prinsip empati dan penerimaan tanpa syarat. Penggunaan istilah kontemporer mengacu pada penggunaan berbagai platform media sosial untuk menjaring publik guna memenuhi tujuan dakwah bakti bagi umat.